Effect of Different Z‐Inducers on the Stabilization of Z Portion in BZ‐DNA Sequence: Correlation Between Experimental and Simulation Data. Issue 11 (14th September 2015) - Pietropaolo, Adriana; D'urso, Alessandro; Purrello, Roberto; Berova, Nina
Abstract In this study we show the outstanding agreement between simulation and experimental data concerning the efficient stabilization effect by NaCl of Z conformation. We demonstrate by circular dichroism (CD) experiments that Na+ not only is able to induce a B to Z form transition in a short (GC)3 alternated portion of a sequence having 17 basis, but also is the best stabilizer in comparison with other Z inducers used (spermine and NiCl2). This result was confirmed by free energy calculations. Chirality 27:773–778, 2015. © 2015 Wiley Periodicals, Inc.